On the effect of stiffness/softness and morphology of interphase phase on the effective elastic properties of three-phase composite material (Fracture and Structural Integrity, 2020)
In the present study, Composite material consisting of an elastic homogeneous isotropic matrix in which are embedded coated elastic isotropic inclusions, widely used in many applications is investigate by homogenization approach coupled to the finite elements method. A finite element model is proposed to predict the Young and Shear modulus of the three-phase composite containing spherical inclusions surrounded by a spherical or ellipsoid interphase layer. Three cases of particles volume fractions and interphase was considered with addition of two interphase morphology. Young modulus of interphase region was varied from soft to hard than the matrix properties. We note that interphase morphology and properties plays an important role in the elastic properties of composite with increasing the volume fraction of inclusions and interphase. The results were compared to the first order bounds Voigt and Reuss, and the mean field homogenization techniques. A sensitive study of the effect of mesh density on the results of the von Mises stresses and elastic properties has been made.
Keywords: Three-component composites; Interphase; Representative volume element; unit cell; Effective elastic properties